Synthesis and Characterization of Nickel(II) Coordination Compounds of 4-[N-(2´ -Hydroxy-1´ -Naphthalidene)amino]antipyrine thiosemicarbazone and 4-[N-(Cinnamalidene) amino]antipyrine thiosemicarbazone - Chakraborti, Indranil (Asian Journal of Chemistry, 2010)
A new series of ten complexes of nickel(Il) of 4-[N-(2'-hydroxy-1'-naphthalidene) amino]antipyrine thiosemicarbazone (HNAAPTS) and 4- [N-(cinnamalidene)amino)antipyrine thiosemicarbazone (CAAPTS) were prepared. The complexes were characterized on the basis of elemental analysis, molecular weight, conductivity, magnetic moment, infrared and electronic spectral data In all the complexes both the thiosemicarbazones act as neutral tridentate (N. N. S) ligands. The coordination number of Ni2+ in these complexes is presumed to be six and have an octahedral geometry.